PELATIHAN PENELITIAN TINDAKAN KELAS DENGAN VARIASI METODE DAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN PENULISAN KARYA ILMIAH GURU-GURU SMK NEGERI 3 YOGYAKARTA - Herminarto Sofyan; Wardan Suyanto; Agus Budiman; Ibnu Siswanto; Agung Gumelar; Wahyu Arya Ruswanto (Universitas Negeri Yogyakarta, 2019)
The Community Service Program (PPM) at SMKN 3 Yogyakarta aims to (1) increase the motivation of teachers to conduct action research and write papers, (2) increase teachers’ ability to select and use appropriate learning methods and media to conduct classroom action research, (3) increase the competence of vocational school teachers in writing scientific papers, (4) increase teachers’ knowledge in accessing scientific journals and conference to publish their work. The activity was attended by 25 participants consisting of 16 productive subject teachers and 9 normative/adaptive subject teachers. The activities carried out in the form of presentation of material about the importance of increasing teacher productivity in publishing scientific work to enhance careers, design action research in the classroom by implementing appropriate media variations and learning methods, writing strategies and publishing articles in journals and proceedings, tutorial guidance on writing articles, and the practice of compiling scientific articles. This PPM activity succeeded in increasing the motivation of teachers to conduct research and write scientific papers, improve the ability of teachers to select the right learning media and methods for conducting classroom action research, increase participants’ ability to write articles, increase teachers’ knowledge in accessing scientific journals and conference to publish their work. Participants satisfy to get new knowledge and skills about classroom action research techniques, they are open-minded and wish to further enhance their ability to conduct classroom action research and write articles to be published in proceedings/journals.